Navigating the Dangers: Critical Evaluation of Maternal Death in Obstetric ICU at DMCH (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Background: Maternal mortality in intensive care units represents the most severe end of the obstetric complication spectrum. Understanding the patterns of delays in care, clinical progression, and outcomes is crucial for improving maternal survival in tertiary care settings.Objective: To critically evaluate maternal deaths in the Obstetric Intensive Care Unit (ICU) of Dhaka Medical College Hospital (DMCH) by analyzing delays in care, management approaches, and the progression from primary to final causes of death.Methods: A retrospective observational study was conducted from January 2024 to December 2024 analyzing 65 maternal deaths in the Obstetric ICU. Data was collected on three types of delays (seeking, reaching, and receiving care), duration of ICU stay, primary management, causes of ICU referral, and progression from primary to final causes of death. Cases were analyzed using the Three Delays Model framework.Results: Delays in seeking care predominated (63.1%, n = 4 ), followed by delays in reaching care (20%, n = 13 and receiving care (16.9%, n = 1 ). The median ICU stay was 24 hours, with 49.2% of deaths occurring within 24 hours of admission. Lower Segment Cesarean Section was the primary management approach (44.6%, n = 29 ). Severe pre-eclampsia and antepartum eclampsia were the leading primary causes (27.7%, n = 18 , while the most common final causes were DIC with/without Acute Kidney Injury (AKI) (23.1%, n = 15 ) and cardiac arrest (21.5%, n = 14 ). Pulmonary edema was the predominant cause for ICU referral (30.8%, n = 20 ).Conclusions: Delays in seeking care significantly impact maternal mortality, with rapid clinical deterioration evident in the high proportion of early ICU deaths. The progression patterns from primary to final causes suggest opportunities for earlier intervention. Improving community awareness, strengthening referral systems, and implementing aggressive early management protocols are crucial for reducing maternal mortality in similar settings.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 69-76